Implementation of health standards in the mitigation of infectious diseases at the class I correctional facility in Malang - Kesya Stevany Santoso; Windi Adelia Gustiara; Daffa Ailla Ardika; Ella Nurlita; Salsabila Varah Lila; Hasna Naifa Putri; Athirah Faqihatun Nisa; Henny Rosalinda (PT WIM Solusi Prima, 2026)
This study analyzes the implementation of the International Health Regulations (IHR) 2005 in mitigating infectious diseases within Indonesian prisons, specifically focusing on Class I Malang Prison. Despite Indonesia recording an average national core capacity score of 75% in the 2023 SPAR, significant gaps remain in surveillance indicators (70%) and health service provision/IPC (60%), particularly in closed institutional settings. Using a qualitative descriptive-analytical method, this research evaluates the impact of participatory socialization in building inmates' political awareness and health literacy. The findings indicate that a bottom-up approach through strengthening inmate participation serves as an effective compensatory mechanism for systemic and facility limitations caused by overcrowding. In conclusion, strengthening national health security requires the integration of prison surveillance systems into the national network and housing policy reforms to structurally reduce the risk of infectious disease transmission.